REPAIR IN "Hitam Putih" TALK SHOW:A Conversation Analysis Study - Anisa Ayu Ambarwaty, - (2011)
The study, entitled Repair in 'Hitam Putih' Talk Show: A Conversation Analysis Study, investigates (1) the patterns of repairs which are evident in "Hitam Putih" talk show, (2) the techniques which are used by the speakers in initiating repairs, and (3) the factors that potentially affect the speakers to initiate repairs. The method used in the present study is qualitative-descriptive. Two episodes of 'Hitam Putih' talk show are obtained as the data of this study. The subjects are the participants in the two episodes of "Hitam Putih" talk show. The identification process of whole conversation is required before the repairs are classified into the appropriate categories. In addition, lexical cohesive relations are also analyzed to find the relation between the repairable segments and the repaired segments. The study reveals that there were totally 55 occurrences of repairs. All types of patterns are recognized in the conversation of the talkshow. Self-initiated, self-repaired pattern appears to be the dominant pattern used by the participants in which they have awareness to repair their own trouble source in speaking. The participants also apply all kinds of the techniques. Repeating part of the utterance occurs as the technique mostly used by the participants. The technique may be identified as the most effective way for the participants to initiate repairs. As for the factor that leads the participants to initiate repairs, a speaker realizes he/she has made a mistake is recognized as the most influencing factor.